2018
DOI: 10.1021/acs.joc.7b01895
|View full text |Cite
|
Sign up to set email alerts
|

Postelongation Strategy for the Introduction of Guanidinium Units in the Main Chain of Helical Oligourea Foldamers

Abstract: The synthesis of hybrid urea-based foldamers containing isosteric guanidinium linkages at selected positions in the sequence is described. We used a postelongation approach whereby the guanidinium moiety is introduced by direct transformation of a parent oligo(urea/thiourea) foldamer precursor. The method involves activation of the thiourea by treatment with methyl iodide and subsequent reaction with amines. To avoid undesired cyclization with the preceding urea moiety, resulting in heterocyclic guanidinium fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Over the years the (oligo)urea backbone has undergone various modifications and the impact of these changes on the structural properties of the new analogs has been investigated. This has led to the conclusion that the 2.5-helical structures of oligoureas are robust and it is possible to substitute the urea residue with γ-amino acid [ 6 , 18 ], carbamate [ 18 , 19 ], thiourea [ 20 ], guanidinium [ 21 ] and also N-methylated [ 22 ] or urea residues with noncanonical substitution patterns [ 23 ] without the loss of the structural integrity of the new molecule. It has also been shown that urea fragments as short as three residues can induce a helical conformation when fused to a peptide too short to fold into a stable secondary structure [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the years the (oligo)urea backbone has undergone various modifications and the impact of these changes on the structural properties of the new analogs has been investigated. This has led to the conclusion that the 2.5-helical structures of oligoureas are robust and it is possible to substitute the urea residue with γ-amino acid [ 6 , 18 ], carbamate [ 18 , 19 ], thiourea [ 20 ], guanidinium [ 21 ] and also N-methylated [ 22 ] or urea residues with noncanonical substitution patterns [ 23 ] without the loss of the structural integrity of the new molecule. It has also been shown that urea fragments as short as three residues can induce a helical conformation when fused to a peptide too short to fold into a stable secondary structure [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are many examples of chemical modification within the urea group in foldamers of this type. There are oligomers where the oxygen atom has been substituted with sulfur or selenium, [35,36,37] or also with nitrogen [37,38] . The NH group, on the other hand, has been replaced with CH 2 [39,40] or oxygen [39,41] .…”
Section: Introductionmentioning
confidence: 99%
“…There are oligomers where the oxygen atom has been substituted with sulfur or selenium, [35,36,37] or also with nitrogen. [37,38] The NH group, on the other hand, has been replaced with CH 2 [39,40] or oxygen. [39,41] The influence of these modifications on the secondary structure has been investigated.…”
Section: Introductionmentioning
confidence: 99%